2015
DOI: 10.1097/prs.0000000000001280
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Features in Koreans with Involutional Blepharoptosis

Abstract: Slightly decreased levator function, infrequent high eyelid crease occurrence, thick and puffy eyelids, low incidence of levator aponeurosis disinsertion from the tarsal plate, and prominent fatty infiltration on the levator muscle are distinct and unique characteristics of involutional ptosis in Korean patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…Eyelids with a short non-fatty-deposit length may require a large amount of levator advancement or another surgical procedure, including combined Müller muscle resection or intraoperative conversion to suspension surgery. The incidence of fatty degeneration in the levator aponeurosis/LPS muscle is quite different among races [3,13]. Previous studies demonstrated fatty degeneration in almost all East Asian patients versus in only 25.6% of Caucasian patients [3,13].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Eyelids with a short non-fatty-deposit length may require a large amount of levator advancement or another surgical procedure, including combined Müller muscle resection or intraoperative conversion to suspension surgery. The incidence of fatty degeneration in the levator aponeurosis/LPS muscle is quite different among races [3,13]. Previous studies demonstrated fatty degeneration in almost all East Asian patients versus in only 25.6% of Caucasian patients [3,13].…”
Section: Discussionmentioning
confidence: 95%
“…Increased fatty deposition in the levator aponeurosis/LPS muscle causes weakness of the tractional force to the upper eyelid [2]. A previous study showed that a fatty deposit in the aponeurosis/LPS muscle is more prevalent in East Asians than in Caucasians [3], suggesting that fatty degeneration has a greater impact on the clinical aspects of aponeurotic blepharoptosis in East Asian patients. As far as we can determine, however, the influence of fatty degeneration on surgical outcomes of transcutaneous aponeurotic repair has not been explored in this population.…”
Section: Introductionmentioning
confidence: 97%
“…The average LF was 8.7 mm, and 24.5% of the eyes were determined to have fair LF. Kim and Lee [22] reported that Korean patients with involutional ptosis had decreased LF compared to Caucasian patients. The authors suggested that decreased LF was another possible mechanism causing involutional ptosis in Koreans and could be attributed to weakening of the levator muscle or aponeurosis itself and heavier eyelids endogenous to Koreans.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there may be some racial differences in the condition of levator aponeurosis. According to a recent report, involutional ptosis results mainly from disinsertion of aponeurosis from the tarsal plate in Caucasians, while the decreased levator function with fatty infiltration is found in Korean patients . Thus, blepharoptosis should be repaired with the consideration of these racial differences.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent report, involutional ptosis results mainly from disinsertion of aponeurosis from the tarsal plate in Caucasians, while the decreased levator function with fatty infiltration is found in Korean patients. 30 Thus, blepharoptosis should be repaired with the consideration of these racial differences. In the absence of definite dermatochalasis, patients with sunken superior sulcus may benefit from HA filler injection or fat graft.…”
Section: Discussionmentioning
confidence: 99%